Myeloid sarcoma, chloroma, or extramedullary acute myeloid leukemia tumor: A tale of misnomers, controversy and the unresolved. (May 2021) - Shallis, Rory M.; Gale, Robert P.; Lazarus, Hillard M.; Roberts, Kenneth B.; Xu, Mina L.; Seropian, Stuart E.; Gore, Steven D.; Podoltsev, Nikolai A.
Abstract: The World Health Organization classification and definition of "myeloid sarcoma" is imprecise and misleading. A more accurate term is "extramedullary acute myeloid leukemia tumor (eAML)." The pathogenesis of eAML has been associated with aberrancy of cellular adhesion molecules, chemokine receptors/ligands and RAS-MAPK/ERK signaling. eAML can present with or without synchronous or metachronous intramedullary acute myeloid leukemia (AML) so a bone marrow evaluation is always recommended. Accurate diagnosis of eAML requires tissue biopsy. eAML confined to one or a few sites is frequently treated with local therapy such as radiotherapy. About 75–90% of patients with isolated eAML will develop metachronous intramedullary AML with a median latency period ranging from 4 to 12 months; thus, patients with isolated eAML may also be treated with systemic anti-leukemia therapy. eAML does not appear to have an independent prognostic impact; selection of post-remission therapy including allogeneic hematopoietic cell transplant (alloHCT) is typically guided by intramedullary disease risk. Management of isolated eAML should be individualized based on patient characteristics as well as eAML location and cytogenetic/molecular features. The role of PET/CT in eAML is also currently being elucidated. Improving outcomes of patients with eAML requires further knowledge of its etiology and mechanism(s) as well as therapeutic approaches beyond conventional chemotherapy, ideally in the context of controlled trials.